Corrigendum to: A bimodal gamma distribution: properties, regression model and applications (Statistics, 54, 469–493). Issue 4 (4th July 2021) - Azimi, Reza; Esmailian, Mahdy
Abstract : Vila et al. proposed and studied a bimodal gamma (BGamma) distribution using a quadratic transformation based on the alpha-skew-normal model. The log-likelihood function and first and second-order partial derivatives are not correct for the case n >1.